Entomological aspects and the role of human behaviour in malaria transmission in a highland region of the Republic of Yemen. (December 2016) - Al-Eryani, Samira; Kelly-Hope, Louise; Harbach, Ralph; Briscoe, Andrew; Barnish, Guy; Azazy, Ahmed; McCall, Philip
Abstract Background The Republic of Yemen has the highest incidence of malaria in the Arabian Peninsula, yet little is known of its vectors or transmission dynamics. Methods A 24-month study of the vectors and related epidemiological aspects of malaria transmission was conducted in two villages in the Taiz region in 2004–2005. Results Cross-sectional blood film surveys recorded an overall malaria infection rate of 15.3 % (250/1638), with highest rates exceeding 30 % in one village in May and December 2005. With one exception, Plasmodium malariae, all infections wereP. falciparum. SevenAnopheles species were identified among 3407 anophelines collected indoors using light traps (LT) and pyrethrum knockdown catches (PKD):Anopheles arabiensis (86.9 %), An. sergentii (9 %), An. azaniae, An. dthali, An. pretoriensis, An. coustani andAn. algeriensis . Sequences for the standard barcode region of the mitochondrialCOI gene confirmed the presence of two morphological forms ofAn. azaniae, the typical form and a previously unrecognized form not immediately identifiable asAn. azaniae . ELISA detectedPlasmodium sporozoites in 0.9 % of 2921An. arabiensis (23P. falciparum, twoP. vivax ) confirming this species as the primary malaria vector in Yemen.Plasmodium falciparum sporozoites were detected inAn. sergentii (2/295) and a single female ofAn. algeriensis, incriminating both species as malaria vectors for the first time in Yemen. A vector in both wet and dry seasons, An. arabiensis was predominantly anthropophilic (human blood index = 0.86) with an entomological inoculation rate of 1.58 infective bites/person/year.Anopheles sergentii fed on cattle (67.3 %) and humans (48.3; 20.7 % mixed both species), but only 14.7 % were found in PKDs, indicating predominantly exophilic behaviour. A GIS analysis of geographic and socio-economic parameters revealed thatAn. arabiensis were significantly higher (P < 0.001) in houses with televisions, most likely due to the popular evening habit of viewing television collectively in houses with open doors and windows. Conclusions The predominantly indoor human biting vectors recorded in this study could be targeted effectively with LLINs, indoor residual spraying and/or insecticide-treated window/door curtains reinforced by education to instil a perception that effective and affordable malaria prevention is achievable.